Identification and implications of relationships among pollutant emission, economic structure and economic growth in China through multivariate analysis - Roujing Jiao; Pingdan Zhang; Song Zhu; Li He; Haipeng Niu (2014)
The relationship between economic growth and environmental quality is generally considered as linear N-shaped or inverse U-shaped curve. However, due to the effects of economic structure on economic growth and pollution emission, this relationship may not be suitable in China. In this study, multivariate regression modelling was performed to identify relationships among pollutant emission, economic structure and economic growth in China. Estimates obtained from integrated multivariate regression results reveal that local provincial economic growth and pollutant emission demonstrate an inverse-N-shaped relationship that is different from that under the Environmental Kuznets Curve (EKC) hypothesis. Further empirical results also indicate that particularly in China: pollutant emission has a negative effect on economic structure and economic growth: pollutant emission has a negative effect on economic structure and economic growth; pollutant emission can reduce the positive contribution of economic structure and economic growth; and enforcement of emission reduction policies could stifle economic transformation and maintain sustainable economic growth.
Keywords: Pollutants